2000
DOI: 10.1038/sj.gt.3301250
|View full text |Cite
|
Sign up to set email alerts
|

Intra-CSF administered recombinant adenovirus causes an immune response-mediated toxicity

Abstract: High doses of adenotk were injected into the cerebrospinal fluid of rats and nonhuman primates (Macaca mulatta). Vector administration was followed by ganciclovir administration for 14 days. Despite the absence of clinical symptoms, analysis of the cerebrospinal fluid (CSF) and histopathological examination of the central nervous system (CNS) of the monkeys (3 weeks after vector injection) were consistent with a viral meningitis. Immunohistochemical analysis of the inflammatory infiltrates in the monkeys revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…[5][6][7] We, and others, have previously shown that injection of viral vectors into the cisterna magna, or trough lumbar puncture, might represent an efficient CNS delivery system in both small (mice) and large (non-human primates) animals. [8][9][10][11] Administration of vector into the cerebrospinal fluid (CSF) circulation, while bypassing the blood-brain barrier, allows viral vector transduction of neuroepithelial cells and delivery of transgene products to the whole CNS through the ventricular circulation. However, viral vector delivery via the CSF circulation still does not represent a realistic gene therapy option for chronic CNS disorders because of the short-term expression and residual immunogenicity of the vectors so far tested (for example, first-generation herpes simplex virus type 1-derived vectors or first generation Ad vectors).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] We, and others, have previously shown that injection of viral vectors into the cisterna magna, or trough lumbar puncture, might represent an efficient CNS delivery system in both small (mice) and large (non-human primates) animals. [8][9][10][11] Administration of vector into the cerebrospinal fluid (CSF) circulation, while bypassing the blood-brain barrier, allows viral vector transduction of neuroepithelial cells and delivery of transgene products to the whole CNS through the ventricular circulation. However, viral vector delivery via the CSF circulation still does not represent a realistic gene therapy option for chronic CNS disorders because of the short-term expression and residual immunogenicity of the vectors so far tested (for example, first-generation herpes simplex virus type 1-derived vectors or first generation Ad vectors).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In vivo administration of Ad vectors is usually associated with dose-dependent toxicity that has been linked to activation of both innate and adaptive immune responses. [3][4][5][6][7][8][9][10][11][12] Systemically administered Ad vector is efficiently distributed to different tissues, [13][14][15][16] exerting its effects both locally and systemically.…”
Section: Introductionmentioning
confidence: 99%
“…46 Vectors can drain from the brain to the neck lymph nodes at least in non-human primates. 47,48 In rodents, drainage to lymph nodes seems to occur after administration into the ventricles, but not following intraparenchymal injection. 45 Given the fact discussed above that rAAV does not induce cellular immunity in laboratory models, even if administered systemically, it is not surprising that it does not elicit cellular immunity, when administered into the CNS of animals either.…”
Section: Immunity In the Cnsmentioning
confidence: 99%